BASALE SIRIH LAYANG NGUBAT REVITALISASI UPACARA BASALE PADA SUKU ANAK DALAM - Nopiansyah, Radius (Paraguna, 2015)
Basaleis  name  ofthe  ritual  of Anak Dalam  Tribe  in Jambi.  There are some function soft his ritual, such  as  wedding  ceremony,  santet  (local  voodoo ),  and medication. Since1978, their Basale's medication ceremony is developed to an art performance  without losing its sanctity  named Basale Sirih Layang  Ngubat.  This performance has been developed  by Darwan Asri  with  Maliki (Alm.),  one  of the leaders of Anak Dalam Tribe in Batanghari Regency of Jambi